Measurement of Indoor Radon Gas Concentration in same Region of Baghdad Governorate Using CR-39 Nuclear Track Detector - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
In this research the activity of radon gas in air in Baghad governorate,Iraq, using “alpha-emitters track registration (CR-39) track detector were measured. This measurement was done for selected areas from Baghdad Governorate, The results obtained shows that the highest average concentrations for Rn-222 is (179.077 Bq/m^3) which was recorded within Al-Shaaib city and less average concentrations was (15.79 Bq/m^3) in the nearby residential area of Baghdad International Airport and the overall average concentrations is (86.508 Bq/m^3) for these regions. Then the radon concentration was measured annual effective dose calculated from radon concentration and found in range from 0.4031 mSv/y to 4.5179 mSv /y with an average value of 2.1824 mSv/y. The annual effective dose of radon was within the allowed international limits.